The effect of loading rate on fracture energy of asphalt mixture at intermediate temperatures and under different loading modes - M.R.M. Aliha; M. Fakhri; E. Haghighat Kharrazi; F. Berto (Fracture and Structural Integrity)
At intermediate service temperatures hot mix asphalt (HMA) concretely are subjected to different loading rates due to movement of vehicles which can significantly affect their mechanical characteristics and final service load. Hence, in this paper the effect of loading rate on intermediate temperature fracture resistance of HMA materials is investigated experimentally in different modes of cracking. Different hot mix asphalt mixtures made of various compositions were subjected to asymmetric threepoint bend loading in the form of edge cracked semi-circular bend (SCB) specimens. The effect of aggregate type and air void were studied on the fracture energy values for three mode mixities (including pure mode I, mixed mode I/II and pure mode II) and at different temperatures of 5°C, 15°C and 25°C. Trends of change in fracture energy values revealed noticeable influence of loading rate on the low and intermediate temperature cracking behavior of tested asphalt mixtures with different air void contents and aggregate types subjected to mixed mode I/II loading. Also, a change observed in fracture resistance of asphalt mixtures at nearly zero (5°C) and intermediate temperatures (25°C) that was due to change in the behavior of bitumen from elastic to viscoelastic.